A Preliminary Investigation of the Intersection of Race and Disabilities among Inmates in the U.S. State Prison System - Baloch, Natasha A. (International journal of offender therapy and comparative criminology, 2019)
The American prison system is overcrowded with minorities in general, and African Americans, in particular. The Department of Justice notes that more than 50% of the prison population have some type of mental disability. In this study, we examine the intersection between race and disabilities in the U.S. State prison system. Using the Rehabilitation Services Administration data set, the study highlights the prevalence and type of disabilities in the prison inmate population. Results demonstrate that African American inmates are overrepresented among inmates with disabilities, are more likely to have mental disabilities relative to physical disabilities, and these results hold for various types of mental disabilities including cognitive, psychosocial, and other mental disabilities. Study limitations and directions for future research are also discussed.